2003
DOI: 10.1105/tpc.017046
|View full text |Cite
|
Sign up to set email alerts
|

IBR5, a Dual-Specificity Phosphatase-Like Protein Modulating Auxin and Abscisic Acid Responsiveness in Arabidopsis

Abstract: Auxin is an important plant hormone that plays significant roles in plant growth and development. Although numerous auxin-response mutants have been identified, auxin signal transduction pathways remain to be fully elucidated. We isolated ibr5 as an Arabidopsis indole-3-butyric acid-response mutant, but it also is less responsive to indole-3-acetic acid, synthetic auxins, auxin transport inhibitors, and the phytohormone abscisic acid. Like certain other auxin-response mutants, ibr5 has a long root and a short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
181
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(198 citation statements)
references
References 81 publications
(89 reference statements)
14
181
0
3
Order By: Relevance
“…A study of ABA-potentiating auxin-mediated repression of embryonic axis elongation suggests that ABA enhances auxin signaling rather than increasing auxin flow or auxin levels (Belin et al, 2009). The auxin signaling-defective mutants axr1 and axr2 have reduced sensitivity to ABA during root elongation (Wilson et al, 1990;Tiryaki and Staswick, 2002;Monroe-Augustus et al, 2003). In another study, transgenic plants overexpressing the H 2 O 2 -inducible gene UGT74E2, which encodes an indole-3-butyric acid (IBA) glucosyltransferase, had elevated levels of both IBA-Glc and free IBA (IAA precursor) and Four-day-old seedlings were transferred to MS medium (Con) or MS medium containing 30 mM ABA, 600 mM GSH, 2.5 mM BSO, 30 mM ABA plus 600 mM GSH, or 30 mM ABA plus 2.5 mM BSO for 2 d before being photographed with a confocal microscope with the same settings.…”
Section: Discussionmentioning
confidence: 99%
“…A study of ABA-potentiating auxin-mediated repression of embryonic axis elongation suggests that ABA enhances auxin signaling rather than increasing auxin flow or auxin levels (Belin et al, 2009). The auxin signaling-defective mutants axr1 and axr2 have reduced sensitivity to ABA during root elongation (Wilson et al, 1990;Tiryaki and Staswick, 2002;Monroe-Augustus et al, 2003). In another study, transgenic plants overexpressing the H 2 O 2 -inducible gene UGT74E2, which encodes an indole-3-butyric acid (IBA) glucosyltransferase, had elevated levels of both IBA-Glc and free IBA (IAA precursor) and Four-day-old seedlings were transferred to MS medium (Con) or MS medium containing 30 mM ABA, 600 mM GSH, 2.5 mM BSO, 30 mM ABA plus 600 mM GSH, or 30 mM ABA plus 2.5 mM BSO for 2 d before being photographed with a confocal microscope with the same settings.…”
Section: Discussionmentioning
confidence: 99%
“…5mARF17 Plants Respond to Auxin Treatment 5mARF17 plants have fewer lateral roots and shorter hypocotyls than control plants ( Figure 4M), traits characteristic of auxinresistant mutants (Estelle and Somerville, 1987;Hobbie and Estelle, 1995;Monroe-Augustus et al, 2003). 5mARF17 plants also have shorter primary roots than control plants ( Figure 4M), whereas auxin-resistant mutants typically have increased root length (Estelle and Somerville, 1987;Hobbie and Estelle, 1995;Monroe-Augustus et al, 2003).…”
Section: Plants Expressing Mir160-resistant Arf17 Have Dramatic Develmentioning
confidence: 99%
“…5mARF17 plants also have shorter primary roots than control plants ( Figure 4M), whereas auxin-resistant mutants typically have increased root length (Estelle and Somerville, 1987;Hobbie and Estelle, 1995;Monroe-Augustus et al, 2003). To determine if the response to exogenous auxin was altered in 5mARF17 plants, we measured root and hypocotyl length after exposing plants to the auxin IAA.…”
Section: Plants Expressing Mir160-resistant Arf17 Have Dramatic Develmentioning
confidence: 99%
“…The ibr5 Arabidopsis mutant which is impaired in a DsPTP gene, is less sensitive to auxin and exhibits the characteristics of some auxin mutants such as a long root and a short hypocotyl when grown in light, fewer lateral roots, aberrant vascular patterning and an increased leaf serration. 113 In a proteomic study, Tyr phosphorylation of the auxin receptor, TIR1, has been reported in reference 35. The double mutant ibr5/tir1 enhances auxin resistance compound compared to that of either parent.…”
Section: 88mentioning
confidence: 99%
“…Involvement of Tyr phosphorylation have been observed in ABA signaling as the DsPTP PHS1 is a negative regulator of ABA transduction pathway whereas IBR5, another DsPTP, has been shown to regulate positively this pathway. 109,113 Moreover, Tyr phosphorylation controls both oxidative stress tolerance and the response to genotoxic stress. Reactive oxygen species are produced during the normal operation of respiratory and photosynthetic electron transport.…”
Section: 88mentioning
confidence: 99%